A super-hydrophobic nano-material water-locking agent and preparation method thereof

By adopting ultra -humidified nano -material unlocking agents formed by the cationic monomer, hydrophobic monomer, fluorine -containing monomer and cross -linked agent, the problem of poor dispersion and short effects of the existing water lock locks is solved. The efficient water unlocking effect.

CN115850553BActive Publication Date: 2025-01-24DAQING OILFIELD CO LTD +1
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202111127077.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-09-26
Publication Date
2025-01-24
Estimated Expiration
2041-09-26

AI Technical Summary

Technical Problem

The existing water-locking agents have poor dispersion and short effective period in aqueous solutions, making it difficult to effectively solve the problem of water locking in tight gas reservoirs.

Method used

Using ultra -humidified nanogenic unlocking agent consisting of cationic monomer, hydrophobic monomer, fluorine -containing monomer, and cross -linked agent to form nano particles of two lovers through convergence, improve its stability and suspension in the water, and pass through through the water, and pass through The electrostatic adsorption of the cedic monomer and the stratum rock extend the effect of the extended water lock agent.

Benefits of technology

To realize the stable dispersing and long -term effects of water locks in water, it significantly improves the penetration rate of rock heart gas phase, and better solves the problem of water locks in the dense gas collection.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The present invention relates to the technical field of tight gas reservoir production increase, and belongs to a super hydrophobic nano material water-desorption lock agent and a preparation method thereof. The present invention solves the problem that modified nano silicon dioxide is poorly dispersible in aqueous solution and is not suitable for field application as a water-desorption lock agent. The water-desorption lock agent comprises the following components by mass fraction: 0.6% to 1% cationic monomer, 10.8% to 17.38% hydrophobic monomer, 2% to 8% fluorine-containing monomer, 0.02% to 0.2% cross-linking agent, and the rest is water. The present invention also discloses a preparation method of the water-desorption lock agent, by introducing hydrophobic monomers and fluorine-containing monomers into cationic monomers, copolymerizing to form a copolymer containing hydrophobic functional groups and hydrophilic functional groups, so that it has good amphiphilicity at the same time, is difficult to agglomerate in water, and obtains a stable nano particle product; it is suitable for field construction, and has good water-desorption lock performance; after entering the formation, the nano particles can be adsorbed on the rock surface by the cationic monomer, which can effectively extend the effective period of water-desorption lock.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of tight gas reservoir production enhancement, and in particular to a super-hydrophobic nano material water-decomposing and locking agent and a preparation method thereof. Background Art

[0002] Tight sandstone gas reservoirs generally have the characteristics of high capillary pressure, strong water sensitivity, small pore throats, poor permeability, and severe heterogeneity. The well fluid can easily enter the reservoir through the water phase capillary self-absorption, making it difficult to return the well fluid and forming water lock damage. Domestic and foreign studies have shown that water lock damage is the most important and most serious type of damage to tight gas reservoirs, with a loss rate of generally 70% to 90%. Once damaged, it will affect the gas well production capacity and recovery rate for a long time.

[0003] At present, common water lock release methods are mainly divided into physical methods and chemical methods. The chemical method has low cost and obvious effect, and is the current research hotspot. For example, CN104449631A (a kind of strong gas wettability nano-silica water lock release agent, its preparation method and rock surface wetting reversal method) discloses the use of gas-wet nano-materials to treat low-permeability oil and gas reservoirs with water lock effect. In this patent, fluorocarbon surfactants are used to modify nano-silica, and then it is configured into a water lock release agent. Fluorocarbon surfactants are used to reverse the rock surface from liquid wettability to strong gas wettability, reduce the viscous resistance of rock surface flow, and improve oil and gas recovery. This method is to change the performance of the rock surface and reduce the viscous resistance of rock surface flow to achieve water lock release. However, in the actual application process, since nano-silica is easy to agglomerate, it is necessary to use organic solvents such as methanol as a dispersant. After being injected into the formation and contacting with fluids such as formation water or well fluid, the performance changes, resulting in poor stability and poor adaptability of water lock release performance. CN102899011A (A low permeability reservoir water-locking agent and its preparation method) uses various surfactants to prepare a water-locking agent with strong surface activity. Although the water-locking agent has strong surface activity and is easy to flow back, when the surfactant flows back with the formation water fluid, the water-locking effect immediately fails and the effective period of the effect is short. Therefore, it is necessary to develop a new water-locking agent to solve the problem that modified nano-silica as a water-locking agent has poor dispersibility in aqueous solution and is not suitable for field application. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of poor dispersibility and short effective period of existing water-locking agents in the prior art, and to provide a super-hydrophobic nano-material water-locking agent and a preparation method thereof; the present invention can cause cationic monomers to produce electrostatic adsorption with formation rocks, effectively extending the effective period of the water-locking agent.

[0005] The invention also discloses a method for preparing a super-hydrophobic nano material water-decomposing and water-locking agent.

[0006] In order to achieve the above-mentioned invention object, the present invention provides the following technical scheme: a super-hydrophobic nano-material water-locking agent, comprising the following components by mass fraction: 0.6%~1% cationic monomer, 10.8%~17.38% hydrophobic monomer, 2%~8% fluorine-containing monomer, 0.02%~0.2% cross-linking agent, and the rest is water.

[0007] Furthermore, the cationic monomer is at least one of dimethyldiallylammonium chloride and methacryloyloxyethyltrimethylammonium chloride.

[0008] Furthermore, the hydrophobic monomer is at least one of styrene, methyl acrylate and butyl acrylate.

[0009] Furthermore, the fluorine-containing monomer is at least one of perfluorobutyl methacrylate, perfluoroheptyl methacrylate, and perfluorooctyl methacrylate.

[0010] The cross-linking agent is one or more of p-phenylene glycol and ethylene glycol dimethacrylate.

[0011] A method for preparing a super-hydrophobic nano-material water-locking agent according to any one of claims 1 to 5, comprising the following steps:

[0012] S1) taking a cationic monomer, a hydrophobic monomer, a fluorinated monomer, and a crosslinking agent according to a formula, and adding them to water to obtain a dispersion having a total mass fraction of 13% to 20% of the cationic monomer, the hydrophobic monomer, the fluorinated monomer, and the crosslinking agent;

[0013] S2) The dispersion obtained in step S1) is heated to 60-80° C., and then an initiator is added and the reaction is kept warm for 4-8 hours to complete the reaction to obtain a dispersion system of the water-decomposing and water-locking agent system.

[0014] Furthermore, the initiator is at least one of potassium persulfate and ammonium persulfate.

[0015] Furthermore, the amount of the initiator added is 0.5% to 2% of the dispersion.

[0016] In the above technical scheme, the mechanism of action of the present invention is to directly copolymerize the hydrophobic monomer and the fluorine-containing monomer with the cationic monomer in water under the crosslinking action of the crosslinking agent to form an amphiphilic copolymer, so that the generated water-locking agent is not easy to agglomerate and grow, forming uniform nanoparticles and maintaining its dispersed state.

[0017] Compared with the prior art, the present invention has the following beneficial effects:

[0018] The present application discloses a super-hydrophobic nano-material water-desorption and locking agent and a preparation method thereof, wherein a hydrophobic monomer and a fluorine-containing monomer are introduced into a cationic monomer, and copolymerized to form amphiphilic nanoparticles, which are difficult to agglomerate in water, thereby obtaining a stable nanoparticle product; at the same time, the density of the obtained nanoparticles is close to that of water, and the nanoparticles can be stably suspended in water, thereby solving the problem of poor dispersibility and suspension of conventional modified nano-silica and other materials, and the cationic monomer can produce electrostatic adsorption with the formation rock, thereby prolonging the effective period of the water-desorption and locking agent.

[0019] Specific implementation methods: The present invention is further described in detail below in conjunction with test examples and specific implementation methods. However, this should not be understood as the scope of the above subject matter of the present invention being limited to the following embodiments, and all technologies implemented based on the content of the present invention belong to the scope of the present invention.

[0020] Example 1

[0021] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.6% dimethyldiallylammonium chloride, 10.8% styrene, 2% perfluorobutyl methacrylate, 0.02% p-phenylene vinyl, 0.5% potassium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0022] S1) taking dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl according to the formula, adding them into water, stirring and dispersing them uniformly, and obtaining a dispersion having a total mass fraction of 13.42% of dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl;

[0023] S2) The dispersion obtained in step S1) is heated to 60° C., potassium persulfate is then added, and after stirring and mixing evenly, the mixture is kept warm for 4 hours to obtain a super-hydrophobic nano-material water-locking agent A.

[0024] Example 2

[0025] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.6% dimethyldiallylammonium chloride, 17.38% styrene, 2% perfluorobutyl methacrylate, 0.02% p-phenylene vinyl, 0.7% potassium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0026] S1) taking dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl according to the formula, adding them into water, stirring and dispersing them uniformly, and obtaining a dispersion liquid with a total mass fraction of dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl being 20%;

[0027] S2) The dispersion obtained in step S1) is heated to 70° C., potassium persulfate is then added, and after stirring and mixing evenly, the mixture is kept warm for 8 hours to complete the reaction and obtain a super-hydrophobic nano-material water-locking agent B.

[0028] Example 3

[0029] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.8% dimethyldiallylammonium chloride, 12% styrene, 4% perfluorobutyl methacrylate, 0.2% p-phenylene glycol, 1% ammonium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0030] S1) taking dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl according to the formula, adding them into water, stirring and dispersing them uniformly, and obtaining a dispersion liquid having a total mass fraction of 17% of dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl;

[0031] S2) The dispersion obtained in step S1) is heated to 70° C., and then ammonium persulfate is added. After stirring and mixing evenly, the mixture is kept warm for 6 hours to obtain a super-hydrophobic nano-material water-locking agent C.

[0032] Example 4

[0033] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 1% dimethyldiallylammonium chloride, 11% styrene, 6% perfluorobutyl methacrylate, 0.1% p-phenylene vinyl, 1.2% ammonium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0034] S1) taking dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl according to the formula, adding them into water, stirring and dispersing them uniformly, and obtaining a dispersion having a total mass fraction of 18.1% of dimethyldiallylammonium chloride, styrene, perfluorobutyl methacrylate, and p-phenylene divinyl;

[0035] S2) The dispersion obtained in step S1) is heated to 80° C., and then ammonium persulfate is added. After stirring and mixing evenly, the mixture is kept warm for 7 hours to complete the reaction to obtain a super-hydrophobic nano-material water-locking agent D.

[0036] Example 5

[0037] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.8% methacryloyloxyethyl trimethyl ammonium chloride, 15% methyl acrylate, 3% perfluoroheptyl methacrylate, 0.2% ethylene glycol dimethacrylate, 1.4% potassium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0038] S1) taking methacryloyloxyethyl trimethyl ammonium chloride, methyl acrylate, perfluoroheptyl methacrylate, and ethylene glycol dimethacrylate according to the formula, adding them into water, stirring and dispersing them uniformly, and obtaining a dispersion liquid in which the total mass fraction of methacryloyloxyethyl trimethyl ammonium chloride, methyl acrylate, perfluoroheptyl methacrylate, and ethylene glycol dimethacrylate is 19%;

[0039] S2) The dispersion obtained in step S1) is heated to 70° C., potassium persulfate is then added, and after stirring and mixing evenly, the mixture is kept warm for 8 hours to complete the reaction to obtain a super-hydrophobic nano-material water-locking agent E.

[0040] Example 6

[0041] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.9% methacryloyloxyethyl trimethyl ammonium chloride, 5% butyl acrylate, 10% styrene, 2% perfluorooctyl methacrylate, 0.08% ethylene glycol dimethacrylate, 0.02% p-phenylene glycol, 1% potassium persulfate, 1% ammonium persulfate, and the balance is water; the water-locking agent is prepared by the following method:

[0042] S1) according to the formula, methacryloyloxyethyl trimethyl ammonium chloride, butyl acrylate, styrene, perfluoroheptyl methacrylate, ethylene glycol dimethacrylate, and phenylene glycol are taken, and added into water, and stirred and dispersed uniformly to obtain a dispersion liquid with a total mass fraction of 18% of methacryloyloxyethyl trimethyl ammonium chloride, butyl acrylate, styrene, perfluoroheptyl methacrylate, ethylene glycol dimethacrylate, and phenylene glycol;

[0043] S2) The dispersion obtained in step S1) is heated to 70° C., and then potassium persulfate and ammonium persulfate are added. After stirring and mixing evenly, the mixture is kept warm for 6 hours to complete the reaction to obtain a super-hydrophobic nano-material water-locking agent F.

[0044] Comparative Example:

[0045] Comparative Example 1

[0046] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.8% dimethyldiallylammonium chloride, 5% perfluorobutyl methacrylate, 0.1% p-phenylene glycol, 1.2% potassium persulfate, and the balance is water;

[0047] The above formula was prepared into comparative example sample 1 according to the preparation method disclosed in Example 3.

[0048] Comparative Example 2

[0049] This embodiment adopts the following formula to prepare the water-locking agent, and the formula is specifically as follows by mass fraction: 0.8% dimethyldiallyl ammonium chloride, 15% styrene, 0.1% p-phenylene vinyl, 1.2% ammonium persulfate, and the balance is water;

[0050] The above formula was prepared into comparative sample 2 according to the preparation method disclosed in Example 3.

[0051] The water lock release agents A to F prepared in the above Examples 1 to 6 and the samples prepared in Comparative Examples 1 to 2 were used to measure the permeability changes of the core samples before and after water lock release through core experiments to evaluate the water lock release effect, i.e., the water lock release rate. The results are as follows:

[0052] Table 1 Water-locking effect of products

[0053] Serial number Water lock release rate (%) Product A 63 Product B 87 Product C 85 Product D 81 Product E 83 Product F 79 Sample 1 54 Sample 2 52

[0054] Through the above examples, the water-locking agent prepared by the present invention can improve the gas permeability of the core by 10% to 30% compared with samples 1 and 2, and better solve the water lock problem of tight gas reservoirs. The preferred embodiments of the present invention are described in detail above, but the present invention is not limited to the specific details in the above embodiments. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, and these simple modifications all belong to the protection scope of the present invention.

[0055] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A super-hydrophobic nano-material water-locking agent, characterized in that: The invention comprises the following components by mass fraction: 0.6% to 1% of cationic monomer, 10.8% to 17.38% of hydrophobic monomer, 2% to 8% of fluorine-containing monomer, 0.02% to 0.2% of crosslinking agent, and the rest is water; The cationic monomer is one or more of dimethyldiallylammonium chloride and methacryloyloxyethyltrimethylammonium chloride; The hydrophobic monomer is one or more of styrene, methyl acrylate, and butyl acrylate; The fluorine-containing monomer is one or more of perfluorobutyl methacrylate, perfluoroheptyl methacrylate, and perfluorooctyl methacrylate; The cross-linking agent is one or more of p-phenylene glycol and ethylene glycol dimethacrylate.

2. A method for preparing a super-hydrophobic nano-material water-locking agent, characterized in that: The preparation method using the super-hydrophobic nano-material water-locking agent according to claim 1 comprises the following steps: S1) taking a cationic monomer, a hydrophobic monomer, a fluorine-containing monomer, and a crosslinking agent according to a formula, and adding them to water to obtain a dispersion having a total mass fraction of 13% to 20% of the cationic monomer, the hydrophobic monomer, the fluorine-containing monomer, and the crosslinking agent; S2) heating the dispersion obtained in step S1) to 60-80° C., then adding an initiator, and keeping the temperature for reaction for 4-8 hours to complete the reaction to obtain a super-hydrophobic nano-material water-locking agent; The initiator is at least one of potassium persulfate and ammonium persulfate; The added amount of the initiator is 0.5% to 2% of the dispersion.

Citation Information

Patent Citations

  • Low-permeability reservoir water-lock releasing agent and preparation method thereof

    CN102899011A

  • Strong gas-wetting nanosilicon dioxide water block removal agent, preparation method thereof and method for wetting transition of rock surface

    CN104449631A